Specifying and verifying sensor networks: An experiment of formal methods - DONG, Jin Song (Institutional Knowledge at Singapore Management University, 2008)
With the development of sensor technology and electronic miniaturization, wireless sensor networks have shown a wide range of promising applications as well as challenges. Early stage sensor network analysis is critical, which allows us to reveal design errors before sensor deployment. Due to their distinguishable features, system specification and verification of sensor networks are highly non-trivial tasks. On the other hand, numerous formal theories and analysis tools have been developed in formal methods community, which may offer a systematic method for formal analysis of sensor networks. This paper presents our attempt on applying formal methods to sensor network specification/verification. An integrated notation named Active Sensor Processes is proposed for high-level specification. Next, we experiment formal verification techniques to reveal design flaws in sensor network applications.